Assessing and Defining Explicit Processes in Visuomotor Adaptation - Heirani Moghaddam, Sarvenaz (Université d'Ottawa / University of Ottawa, 2020)
The Process Dissociation Procedure (PDP) and Verbal Report Framework (VRF) have demonstrated that both explicit (Explicit Adaptation, EA) and implicit processes (Implicit Adaptation, IA) contribute to visuomotor adaptation. However, the definition of EA is inconsistent across the two paradigms, such that the PDP refers to EA as reflecting one’s knowledge regarding how they have to reach in the novel visuomotor environment, while the VRF refers to EA as reflecting pre-planned aiming strategies. The objective of the current experiment was to compare EA as assessed via the PDP and VRF and hence provide insight into if they are assessing similar explicit processes. Sixty-one participants were evenly divided into three groups (PDP, VRF and VRF-No Cursor) and trained to reach in a virtual environment with an aligned cursor (1 block of 45 trials) and then a cursor rotated 40° clockwise (CW) relative to hand motion (3 blocks of 45 trials). EA and IA were assessed immediately following each block of rotated reach training trials, and again 5-minutes later. In the assessment trials, the PDP group reached while using any learned strategy (EA+IA), or while not engaging in a strategy (IA) and the VRF group reported their planned aiming direction by picking a number from an array of numbers surrounding the target (EA), before reaching to the target (EA+IA) with visual feedback. The VRF-No Cursor group completed the same assessment trials as the VRF group, but no visual feedback was presented during assessment of EA and IA. Following this, participants completed a post-experiment questionnaire and a drawing task to assess their awareness of the visuomotor rotation and changes in their reaches respectively. We found that all groups adapted their reaches to the 40° CW cursor rotation. As well, averaged across participants, the magnitude and retention of EA and IA were similar between the PDP and VRF groups. However, the magnitude of EA established via the VRF was not related to participants’ post-experiment awareness of the visuomotor distortion and how they had changed their reaches, as observed in the PDP and VRF No-Cursor groups. Together, these results indicate that, while the PDP and VRF suggest similar contributions of EA and IA to visuomotor adaptation, the methods of assessment engage different explicit processes. EA assessed within the VRF does not reflect one’s awareness of the visuomotor distortion at the end of the experiment or how they changed their reaches.
Keywords: Visuomotor Adaptation; Process Dissociation Procedure; Verbal Report Framework; Explicit; Implicit